The Effect of the Convergent Nozzle Fan on Air Pressure - X.A. Nurxonov; A.A. Ravshanov; F.K. Khudaykulov; U.A. Hamidov; F.M. Bo‘riyev (Scientific Trends, 2025)
This paper discusses the influence of a convergent nozzle (confusor) on the pressure and flow characteristics of axial fans. It explains how the addition of a convergent nozzle increases the air velocity and enhances the ejection effect while partially reducing the fan’s overall capacity and static pressure. The study presents mathematical relationships describing pressure drop, outlet resistance, and total aerodynamic resistance, highlighting the role of geometric parameters such as the nozzle’s contraction angle and cross-sectional area ratio. The pressure–flow (ΔP–Q) characteristics of fans with and without a convergent nozzle are compared to demonstrate performance differences. The results show that, despite a slight reduction in airflow, the use of a convergent nozzle can significantly improve energy efficiency and flow stabilization when appropriately designed.
Keywords: Convergent nozzle, confusor fan, air pressure, airflow rate, outlet resistance, aerodynamic efficiency, pressure–flow characteristics, contraction resistance, diffuser effect, ventilation systems.